Quality and power in the supply chain what industry does for the sake of quality - Lamprecht, James L., 1947-
This book reconciles two divergent worlds for the beleaguered quality manager. The first is that of quality and managerial fads, promoted by quality professionals and the quality 'industry' - with its seminars, certification programs and the pressures of an ever increasing number of international standards, state and national legislation and powerful corporations. The second is a virtual antithesis to this world of mission statements, quality policies, procedures and statistical techniques, and is embodied in the international phenomenon that is the Dilbert (TM) cartoon strip. Across America a.